2006
DOI: 10.1103/physrevb.73.045304
|View full text |Cite
|
Sign up to set email alerts
|

Spin relaxation in lateral quantum dots: Effects of spin-orbit interaction

Abstract: We report results of calculations of the effect of spin-orbit interaction on electron spin relaxation in a lateral quantum dot. Our study is motivated by puzzling results of high source-drain transport measurements of singlet-triplet transitions of two electrons in lateral and vertical devices that show a strong asymmetry as a function of the applied magnetic field. Using exact diagonalization techniques, we investigate the influence of the spin-orbit interaction on the energy levels of a two-electron droplet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 52 publications
5
48
0
Order By: Relevance
“…In particular, Hanson et al found T 1 for the singlet-triplet transition in a two-electron GaAs dot to be 2.6 ms at B=0.02 T. We shall call this T ST . Extensive theoretical work has been done for T ST in GaAs 4,13,14,15,16 and our methods are similar to those found in these references.…”
Section: Introductionmentioning
confidence: 78%
“…In particular, Hanson et al found T 1 for the singlet-triplet transition in a two-electron GaAs dot to be 2.6 ms at B=0.02 T. We shall call this T ST . Extensive theoretical work has been done for T ST in GaAs 4,13,14,15,16 and our methods are similar to those found in these references.…”
Section: Introductionmentioning
confidence: 78%
“…In contrast to single-electron spin states in a quantum dot, the lowest two-electron spin states, singlet and triplet, are coupled directly by the spin-orbit interaction ͓ex-cept for T 0 and S, which are not coupled to lowest order in the spin-orbit interaction, due to spin selection rules ͑Dickmann and Hawrylak, 2003;Florescu and Hawrylak, 2006;Sasaki et al, 2006;Climente et al, 2007;Golovach et al, 2007͔͒. This is not so surprising since the singlet and triplet states themselves involve different orbitals.…”
Section: Spin-orbit Interaction In Quantum Dotsmentioning
confidence: 99%
“…[4][5][6] On the other hand, at higher fields ͑Teslas͒ the relaxation is due to phonon-induced spin-flip transitions. [7][8][9][10][11][12][13][14][15][16][17][18][19] These are allowed due to the presence of spin-orbit coupling. Variants of the phonon-induced spin relaxation has been proposed, such as ripple coupling, 20,21 important in very small quantum dots ͑10 nm͒, or fluctuations in spin-orbit parameters, important when underlying heterostructure inhomogeneities 22 are present.…”
Section: Introductionmentioning
confidence: 99%